UJI KINERJA ALAT PENGERING HYBRID TIPE LORONG UNTUK PENGERINGAN BIJI KAKAO (Theobroma caccao Linn) - Rianti, Risa; Kahar, Kahar; Anisum, Anisum (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2018)
Research aimed determine the total energy received by the hybrid solar tunnel dryer, and to determine the efficiency of the hybrid solar tunnel dryer. The research method was an experiment method. Date retrieve procedures include: intensity of solar radiation, the room temperature of drying, furnaces temperature and ambient temperature. The research result shows that the total heating energy of material is 45.73 kJ, evaporation energy of material is 694.40 kJ, and the air heating energy is 25.21 kJ. The thermal efficiency of hybrid dryer is 14.09%, furnace efficiency is 18.78% and total efficiency is 15.82%. Keywords: hybrid solar tunnel dryer, efficiency, total energy.